Chemical Exposure Due to Anthropogenic Ocean Acidification Increases Risks for Estuarine Calcifiers in the Salish Sea: Biogeochemical Model Scenarios - Bednaršek, Nina; Pelletier, Greg; Ahmed, Anise; Feely, Richard A. (Frontiers in Marine Science, 2020)
Ocean acidification is projected to have profound impacts on marine ecosystems and resources, especially in the estuarine habitats. Here, we describe biological risks under current exposure of anthropogenic ocean acidification in the Salish Sea, an estuarine system that already experiences inherently low OA conditions. We used the PNNL/DOE Salish Sea biogeochemical model (SSM) informed by a selection of OA-related biological thresholds of ecologically and economically important calcifiers, pteropods and Dungeness crabs. The SSM was implemented to assess current exposure and associated risk due to reduced aragonite saturation state (Ωar) and pH conditions with respect to the magnitude, duration and severity of exposure below the biological thresholds in the Salish Sea and compare it to the pre-industrial time. We further investigated individual effects of atmospheric CO2 uptake and nutrient-driven eutrophication on the changes in the chemical exposure since the pre-industrial time. Our model predicts an average decrease in Ωar of about 0.11 and average decrease in pH of about 0.06 in the top 100 m of the water column of the Salish Sea since the pre-industrial times that predispose pelagic calcifiers to increased magnitude, duration and severity of exposure. Accordingly, we demonstrate that present-day exposure is below the thresholds for pteropod sublethal effects across the entire Salish Sea basin, while mortality threshold exposure occurs on a spatially limited basis. The greatest risk for the larval Dungeness crabs is associated with the spatially limited exposures to low calcite saturation state in the South Sound in the springtime, where an increase in internal dissolution could induce additional energetic costs. The main anthropogenic driver behind the predicted impacts is atmospheric CO2 uptake, while nutrient-driven eutrophication plays only a marginal role over spatially and temporally limited scales. Reduction of CO2 emissions can help sustain biological species vital for ecosystem functions and society.